Implications of the New Criminal Code on the Narcotics Law: An Analysis of Reformulation Needs - Endi Arofa; Tubagus Ahmad Ramadan (PT Justitia Legal Research, 2025)
This study analyzes the implications of the enactment of Law Number 1 of 2023 concerning the Criminal Code on the enactment of Law Number 35 of 2009 concerning Narcotics and the urgency of the necessary reformulation. Using normative juridical methods through legislative and conceptual approaches, this study examines the legal substance, legal principles, and doctrines relevant to the harmonization of the two regulations. The results of the study show that the revocation of Articles 111 to 126 of the Narcotics Law by Article 622 paragraph (1) letter w of the new Criminal Code creates a substantial legal vacuum for the regulation of the crime of cultivation, buying and selling and distributing narcotics that is not fully accommodated in the new Criminal Code. There is a significant disharmony between the orientation of restorative punishment in the new Criminal Code and the retributive approach in the Narcotics Law, as well as inconsistencies in the implementation of rehabilitative approaches for narcotics users and addicts. This study concludes that the reformulation of the Narcotics Law is an urgent need to fill the legal vacuum, harmonize the criminal paradigm, strengthen the special investigation mechanism, and implement a balance between the eradication of illicit circulation and the protection of human rights in an integrated and fair criminal justice system.